Sexual Behavior and Semen Quality of Crossbred Bulls after Supplementation of Flaxseed and with Rubber Mat Floor - Ali, Samir Humeida; Mohanty, Tushar Kumar; Sinha, Ranjana; Singh, Pawan; C, Kotresh Prasad; Bhakat, Mukesh; Panchabai, Girish (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The experiment was conducted to study the effect of dietary supplementation of flaxseed and bedding material on sexual behavior,libido, and semen quality of crossbred bulls. For this, seventeen mature healthy breeding bulls were assigned to three groups as G1, G2,and G3 with 6, 5, 6 bulls, respectively. The bulls of G1 were fed as per standard diet (ICAR, 2013) and served as control. Bulls of G2 werefed as per standard diet G1 plus roasted flaxseed @ 1 kg/bull/day for 120 days, and bulls of G3 were provided rubber mat as beddingmaterial and fed as per G2. The libido of the bulls was assessed by sexual behavior parameters and hormonal profile, and the seminalquality was examined. Significant (P
Keywords: : Crossbred bulls; Roasted flaxseed; , Rubber mat; Libido; Semen quality; Sexual behavior